Algorithmic approach for clandestine localisation and tracking in short-range environments. (1st January 2012) - Al-Kuwari, Saif; Wolthusen, Stephen D.
Target tracking applications have recently evolved becoming essential intelligence and law enforcement tools. Traditionally, long-range communications, such as cellular networks, have been used for this purpose. Such conventional tracking approach, however, usually suffers from several accuracy implications due to location measurement errors. This is exemplified in densely cluttered and indoor environments where measurements are severely affected by excessive environmental and physical noise. Additionally, most localisation and tracking mechanisms today are based on active approach where targets actively cooperate in the tracking process, or at least are aware of it. Clearly, such approach is not suitable for law enforcement applications where targets are suspects or criminals. In this paper, we adopt an algorithmic approach to build an agent-based passive tracking system. We develop a number of algorithms to initiate and maintain this tracking system while consistently preserving passivity.